Effect of Thermo-Stress on Morpho-Phenological and Reproductive Behaviour of Groundnut (Arachis hypogaea L.) - Dash, Deepali; Chimmad, V. P. (International Journal of Economic Plants, 2021)
Global warming is defined as the change in climate in terms of increased frequency of extreme weather events as well as increased air temperature and vapour pressure deficit of air, spatial and temporal change in rainfall. In spite of beneficial effect of increased atmospheric CO2 concentration, climate change will adversely impact the production and productivity of groundnut grown in subtropical and tropical regions of the world. Increasing temperature in present day is the headache for the agricultural sectors. Most of the agricultural food crops are affected badly due to the temperature stress. Crop production is limiting due to the harsh effect of drought and thermo-stress. Groundnut (Arachis hypogaea L.), the king of oilseeds having a rich source of polyunsaturated fatty acids (oleic and linoleic acids) is in demand among people due to its good quality protein, oil, minerals and vitamins. It also shows a drastic change in their vegetative and reproductive stage when exposed to high temperature stress. In the present review we will discuss about different morpho-phenological and reproductive changes occur when temperature stress will coincide with the different growth period of groundnut.